2003
DOI: 10.1021/jf030201x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Soluble and Micelle-Bound Heat-Induced Protein Aggregates on Network Formation in Acid Skim Milk Gels

Abstract: Gel formation was monitored by low amplitude rheometry during acidification at 40 degrees C with 1.5% glucono-delta-lactone in combined milk systems containing soluble and/or micelle-bound heat-induced (95 degrees C/10 min) aggregates of denatured whey proteins and kappa-casein and in heated dairy mixes with varying micellar casein/whey protein ratio (CN/WP). Both soluble and micelle-bound aggregates increased gelation pH and gel strength. Micelle-bound aggregates seemed to modify the micelle surface so that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 32 publications
8
70
0
Order By: Relevance
“…The impact of heat-induced whey protein denaturation on gel firmness is still a subject of intensive discussion. [43][44][45][46] The bonds involved are either covalent disulfide bonds or hydrophobic interactions. Some researchers 44,47 reported that addition of a thiol-blocking agent caused a considerable decrease in G′, indicating the importance of disulfide bonds on gel firmness.…”
Section: Effects Of Concentration and Incubation Timementioning
confidence: 99%
“…The impact of heat-induced whey protein denaturation on gel firmness is still a subject of intensive discussion. [43][44][45][46] The bonds involved are either covalent disulfide bonds or hydrophobic interactions. Some researchers 44,47 reported that addition of a thiol-blocking agent caused a considerable decrease in G′, indicating the importance of disulfide bonds on gel firmness.…”
Section: Effects Of Concentration and Incubation Timementioning
confidence: 99%
“…Indeed, it has been shown that heat treatment of milk induces the formation of κ-casein-β-lactoglobulin complexes that are responsible for a higher value of the gelation pH [10,17,28]. For higher levels of mineral depletions, the pH of milk before heat treatment and the heat-induced κ-casein dissociation no longer increased.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, by decreasing the casein to whey protein ratio of milk blends, Guyomarc'h et al (2003a), Puvanenthiran et al (2002) or Beaulieu et al (1999) increased the size of complexes up to fivefold and obtained acid gels with proportionally increased final G' values. In model whey protein systems, higher protein concentration also promotes formation of larger complexes Ju and Kilara 1998b;Le Bon et al 1999).…”
Section: Possible Methods To Modify the Size Of The Heat-induced Wheymentioning
confidence: 99%
“…Disulphide covalent bonds have also been evidenced to sustain the acid gels' network (Hinrichs and Keim 2007) as a result of the formation of heat-induced whey protein/κ-casein complexes on heating the milk. Covalent bonds are thought to account for the increased elastic modulus G' and lower tanδ of acid gels made with heated milk (Guyomarc'h et al 2003a). Vasbinder et al (2004) further showed that thiol/disulphide exchanges occur throughout acidification of milk where heatinduced complexes are present and evidenced that disulphide bonds contribute to the increase in G' on gel formation.…”
Section: Structure and Mechanical Properties Of Acid Dairy Gelsmentioning
confidence: 99%
See 1 more Smart Citation